Etnisitas Masyarakat Tionghoa di Kampung Cino Kota Padang, 1998-2022 - Ayu Putri; Salsabila Yumna al-Insyi; Wendi Fernandez; Syamsul Badri (Local History & Heritage, 2022)
This article describes the ethnicity of the people of Kampung Cino in Padang City. This research uses historical methods through data collection techniques from interviews. The results of the interviews were then supplemented with written data sources. The findings of this article explain the history of Chinese ethnicity and cultural differences that the life of ethnic Chinese in Cino Village, Padang City shows that they can blend in life without losing their identity, they still maintain their existence, especially in the economic sector. In addition, this research will also show whether there are conflicts that occur during the process of adaptation to the existence of this ethnicity.